Differences in News Translation between Broadcasting and Newspapers: A Case Study of Korean-English Translation - Lee, Chang-soo (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThe aim of the study is to look into differences between broadcasting and newspaper news translation in their approaches to rendering the lead of the news report. For this purpose, the study analyzes shifts in English translations of Korean newspaper reports and compares them with the results of a previous study on broadcasting translation. The analysis suggests that while lead reduction is characteristic of broadcasting translation, lead expansion figures more prominently in newspaper translation. The paper gives a detailed account of these differences and offers some tentative explanations about what gives rise to them. It also discusses the differences in terms of the degree of latitude the translator exercises in editing the TT and their implications for different roles played by the translator in the two modes of translation.